The COVID-19 Pandemic Response System at University Level: The Case of Safe Campus Model at Ewha Womans University - Kyunghee Jung-Choi; Nackmoon Sung; Sun Hwa Lee; Misun Chang; Hee Jung Choi; Chung-Jong Kim; Nam-Kyong Choi; Hanna Kim; Yi-Jun Kim; Whanhee Lee; Hyesook Park; Eunhee Ha (The Ewha Medical Journal)
In response to the changes in the Coronavirus disease 2019 (COVID-19) epidemic situation, Ewha Womans University established Ewha Safe Campus (ESC), an on-campus infection outbreak management system, to allow students and faculty members to safely resume face-to face classes in 2022. The COVID-19 testing station, Ewha Safe Station, is the core element of ESC. Symptomatic students and faculty members perform a combo swab self-PCR test or receive a nasopharyngeal swab PCR test from experts to prevent the spread of COVID-19 through early detection and management. ESC is significant in that it detects infection risks and proactively implements preemptive measures in a university. The COVID-19 health response system model at the university level was applied for the first time in South Korea, reaching a milestone in the history of university health in South Korea. In particular, it is highly valuable that the test was free of charge, as it enabled all of the examinees to have easy access to the test through joint cooperation with the Seegene Medical Foundation. This is a successful example of cooperation between schools and private institutions for public health improvement. In the future, the direct and indirect effects of the establishment and implementation of ESC need to be evaluated and confirmed, and areas requiring improvements need to be identified in preparation for another infectious disease outbreak in the future.